2017
DOI: 10.1097/mib.0000000000001056
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Fecal Incontinence in Women of Childbearing Age with Crohnʼs Disease

Abstract: Fecal incontinence is a significant complaint in at least one-third of women of childbearing age with Crohn's disease. Patients'disease and treatment histories seem to have a comparable effect to their childbirth history concerning the presence of fecal incontinence. Both physicians and surgeons who are involved in the management of Crohn's disease need to keep this in mind.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 21 publications
2
17
0
1
Order By: Relevance
“…Faecal incontinence, usually defined as the uncontrolled loss or liquid of solid stool, is one of the concerns reported by IBD‐patients . Its prevalence amongst the IBD‐population, which has only been investigated in five studies to date, is estimated between 20% and 38% in tertiary centers and even up to 74% in a community‐based population . The latter has only been reported once, precluding reliable data on community‐based prevalence numbers of faecal incontinence and its association with quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Faecal incontinence, usually defined as the uncontrolled loss or liquid of solid stool, is one of the concerns reported by IBD‐patients . Its prevalence amongst the IBD‐population, which has only been investigated in five studies to date, is estimated between 20% and 38% in tertiary centers and even up to 74% in a community‐based population . The latter has only been reported once, precluding reliable data on community‐based prevalence numbers of faecal incontinence and its association with quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Some focused only on female participants to determine the role of childbirth in IBDrelated FI 18,19 . Some reported both patients with UC and CD whilst others included either CD or UC patients alone.…”
Section: Resultsmentioning
confidence: 99%
“…Others found that this difference was nonsignificant 21 . Patients with a longer disease duration were at greater risk of FI 18 . This relationship was non-significant in another study 20 .…”
Section: Duration and Type Of Ibdmentioning
confidence: 95%
See 2 more Smart Citations